Effect of powder feeding rate on heat and mass transfer behaviors during filler powder laser welding. (December 2019) - Lu, Cheng; Lin, Qida; Li, Bin; Wu, Jiazhu; Zhang, Yi
Highlights: The effect of powder feeding rate on plasma was investigated. The curve of inverse bremsstrahlung absorption and keyhole depth was obtained. The reason for the variation in keyhole area was explained by calculating plasma pressure. The curve of powder feeding rate and molten pool temperature is similar to a linear line. Abstract: The heat and mass transfer behavior is the influencing factor of welding quality, during filler powder laser welding. The characteristics of plasma and keyhole can characterize the heat and mass transfer behavior. Experimental platforms were built to observe the effect of powder feeding rate on the heat and mass transfer behavior. The main results of the experiment are as follows. In the process of filler powder laser welding, the keyhole depth and fusion depth were improved by selecting the critical value of powder feeding rate 5 g/min as the welding process parameter. When the powder feeding rate exceeded the critical value, the electron temperature and electron density decreased and increased respectively. The keyhole depth decreased with the increase of the inverse bremsstrahlung absorption coefficient of the keyhole plasma at the top of the keyhole. The keyhole area increased with the increase of plasma pressure at the keyhole opening. The inverse bremsstrahlung absorption of plasma plume and the number of powder particles sprayed into the molten pool were the factors that caused the decrease of the surface temperature and the length of the molten pool.